Haraz Dairy Milk Mini Mart / Hafiy Raziq Norikhan - Hafiy Raziq, Norikhan (2020)
The Dairy industry has a great future prospect as it is a necessity for customers including all stage of ages. Nowadays, people using most of their energy to contribute their works and daily routine activities. Therefore, I have established this company in order to fulfill the needs and help them to treat their health and fitness. This company will be on 1 January 2021 by me and moral supports from family and members. I have decided to establish and register this company as a single ownership and also a sole proprietorship. I believe that single ownership has many advantages compared to other type of business. Dairy business which provides services and sales product in terms of healthy product. This company main business is to sales and give the quality taste of milk and good nutrients to people body. Besides this compony provide high quality of milk and serves many types of product based on milk. I believe that would attract more customers once they have gone through the experience and the taste of our product. The business’s main strength is the taste of high-quality milk. This product quality is based on how it makes and how the taste can be in various. This company take serious in keeping the product in good condition because I want people to taste the product with safe and help them to continue their daily routine with good nutrients in the body.